Report of the Commission on Narcotic Drugs on the Fifty-Seventh Session (13 December 2013 and 13-21 March 2014) - United Nations (United Nations, 2014)
This is the official record of the report of the Commission on Narcotic Drugs on its fifty-seventh session for the period of 13 December 2013 and 13-21 March 2014.